2018
DOI: 10.1371/journal.pgen.1007630
|View full text |Cite
|
Sign up to set email alerts
|

The uterine epithelial loss of Pten is inefficient to induce endometrial cancer with intact stromal Pten

Abstract: Mutation of the tumor suppressor Pten often leads to tumorigenesis in various organs including the uterus. We previously showed that Pten deletion in the mouse uterus using a Pgr-Cre driver (Ptenf/fPgrCre/+) results in rapid development of endometrial carcinoma (EMC) with full penetration. We also reported that Pten deletion in the stroma and myometrium using Amhr2-Cre failed to initiate EMC. Since the Ptenf/fPgrCre/+ uterine epithelium was primarily affected by tumorigenesis despite its loss in both the epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Our recent publications in PNAS (1,2) describe the phenotypic effects of loss of activin-like kinase 5; transforming growth factor β receptor 1 (ALK5;TGFBR1) or Smad2 and Smad3 in the mouse uterus and are accompanied by a commentary by Li (3). Our conclusions are that this pathway acts as a tumor suppressor pathway, findings that are also supported by a recent paper (4). We appreciate the letter to the editor by Liu et al (5); however, their analysis is performed utilizing data from uterine cancer samples from The Cancer Genome Atlas (TCGA) and should be cautiously interpreted for the following reasons:…”
supporting
confidence: 73%
“…Our recent publications in PNAS (1,2) describe the phenotypic effects of loss of activin-like kinase 5; transforming growth factor β receptor 1 (ALK5;TGFBR1) or Smad2 and Smad3 in the mouse uterus and are accompanied by a commentary by Li (3). Our conclusions are that this pathway acts as a tumor suppressor pathway, findings that are also supported by a recent paper (4). We appreciate the letter to the editor by Liu et al (5); however, their analysis is performed utilizing data from uterine cancer samples from The Cancer Genome Atlas (TCGA) and should be cautiously interpreted for the following reasons:…”
supporting
confidence: 73%
“…We conclude that Fbxw7/Pten tumors begin as usual-type endometrioid adenocarcinomas, but evolve in a surprisingly stereotypical manner between 12 and 48 wk into definitive UCS. This is remarkable, as UCS has not been reported among prior mouse models of EC, many of which were based on Pten or Trp53 (35, 3941). These findings thus point to Fbxw7 as a specific driver of UCS.…”
Section: Resultsmentioning
confidence: 97%
“…Since triple-gene mutant cells were mostly negative for PGR, P4 likely represses endometrial carcinogenesis by acting through stromal cells as found in the normal uterus ( 64 69 ). Additionally, normal epithelial cells adjacent to mutant epithelial cells appear to play a critical role in repressing the progression of EECs because aggressive epithelial lesions developed when Pten was mutated in the entire uterine epithelium by Ltf iCr e ( 70 ). To develop preventive and therapeutic treatments for EECs, it is crucial to elucidate the molecular mechanisms underlying the tumor-repressing effects of the normal endometrial environment and steroid hormones.…”
Section: Discussionmentioning
confidence: 99%